Latent profiles and trajectories of family functioning: a risk and resilience approach to child maltreatment prevention and promotion of early achievement - Prendergast, Sarah, author; MacPhee, David, advisor; Carcasson, Martin, committee member; Coatsworth, Doug, committee member; Riggs, Nathaniel, committee member (Colorado State University. Libraries, 2019)
Child maltreatment and being unready to learn at kindergarten entry are two societal problems that are associated with children's later development. Children are at highest risk for maltreatment during the first four years of life; importantly, this is the same period in which children gain cognitive and social skills critical for early achievement. Despite progress, rates of maltreatment remain high and costly to treat, and economic and ethnic disparities in early achievement persist. Grounded in ecological theory, this dissertation explored trajectories and classes of family functioning across various levels of risk at birth. In Study 1, change in income, maternal education, and parenting stress, as well as neighborhood social cohesion, were tested as predictors of initial levels of maternal aggression and change over time. The results indicated that associations among the predictors and maternal aggression differed across level of risk. In Study 2, cumulative family risk and latent classes of family risk at birth were explored as predictors of kindergarten outcomes and self-reported involvement with Child Protective Services. The results demonstrated that cumulative risk and three latent classes of family risk differentially predicted all outcomes. Several policy and programmatic implications are discussed related to ecological models of prevention, the merits of cumulative risk and risk combinations, and tailored intervention strategies.